Front-Presented Looming Sound Selectively Alters the Perceived Size of a Visual Looming Object. (July 2018) - Yamasaki, Daiki; Miyoshi, Kiyofumi; Altmann, Christian F.; Ashida, Hiroshi
In spite of accumulating evidence for the spatial rule governing cross-modal interaction according to the spatial consistency of stimuli, it is still unclear whether 3D spatial consistency (i.e., front/rear of the body) of stimuli also regulates audiovisual interaction. We investigated how sounds with increasing/decreasing intensity (looming/receding sound) presented from the front and rear space of the body impact the size perception of a dynamic visual object. Participants performed a size-matching task (Experiments 1 and 2) and a size adjustment task (Experiment 3) of visual stimuli with increasing/decreasing diameter, while being exposed to a front- or rear-presented sound with increasing/decreasing intensity. Throughout these experiments, we demonstrated that only the front-presented looming sound caused overestimation of the spatially consistent looming visual stimulus in size, but not of the spatially inconsistent and the receding visual stimulus. The receding sound had no significant effect on vision. Our results revealed that looming sound alters dynamic visual size perception depending on the consistency in the approaching quality and the front–rear spatial location of audiovisual stimuli, suggesting that the human brain differently processes audiovisual inputs based on their 3D spatial consistency. This selective interaction between looming signals should contribute to faster detection of approaching threats. Our findings extend the spatial rule governing audiovisual interaction into 3D space.